Assessing cage culture potentiality of long whiskers catfish, Mystus gulio (Hamilton, 1822) in relation to climate change adaptation in Bangladesh coast. Issue 3 (3rd July 2022) - Hossain, Mohammad; Mostafiz, Md.; Ahamed, Saokat; Hassan, Mohammed; Islam, Md.; Baten, Md.; Hoq, Md.; Akter, Taslima
ABSTRACT: Climate change-induced sea-level rise, salinity intrusion, sudden water surge, natural calamities, etc. affect the fish biodiversity, food security, and coastal livelihoods that highlight the necessities of developing climate-resilient strategies e.g. adaptive aquaculture techniques. Cage culture of salinity-tolerant fish may be an adaptation strategy to compensate for the losses of freshwater fish production by climate change in coastal areas. Therefore, a 120-day long field experiment was conducted to evaluate the cage culture potentiality of Mystus gulio in the coastal region of Bangladesh. Three treatments at the stocking density of 90 (T1 ), 135 (T2 ), and 180 (T3 )/m 2 were stocked in nine cages (1.115 m 2 ). Significantly ( p <0.05) higher growth performance and feed utilization were recorded in T1 followed by T2 and T3 . In return, considering overall growth, survival, production, coast-benefit analysis, T2 was found more profitable followed by T3 and T1 . This result revealed that the culture of M. gulio in floating net cages might be a potential climate-adaptive aquaculture technique in the coastal region. However, further research works are necessary for optimizing stocking density, nutrition, social acceptance, etc. before conclude it as a viable climate-resilient adaptive aquaculture practice.